2012
DOI: 10.1097/jom.0b013e31824af5a8
|View full text |Cite
|
Sign up to set email alerts
|

Can a Single-Item Measure Assess Physical Load at Work? An Analysis From the GAZEL Cohort

Abstract: Perceived physical strain approximates physical load in the absence of detailed measures. Perceived physical strain could be used in nonoccupational epidemiologic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…According to previous studies self-administered questionnaires are able to classify participants to sedentary or standing work and low or high workload in acceptable accordance with interview [ 28 ] and observational [ 29 ] data. Furthermore Sabbath et al concluded that a single item question was a fairly good indicator of physical load at work compared to a 38-item questionnaire [ 30 ]. The authors found the single item work related physical activity question to be sensitive enough to detect increased levels of work related physical activity within a certain task, for example lifting or pulling, and also to detect overall increases in total work related physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies self-administered questionnaires are able to classify participants to sedentary or standing work and low or high workload in acceptable accordance with interview [ 28 ] and observational [ 29 ] data. Furthermore Sabbath et al concluded that a single item question was a fairly good indicator of physical load at work compared to a 38-item questionnaire [ 30 ]. The authors found the single item work related physical activity question to be sensitive enough to detect increased levels of work related physical activity within a certain task, for example lifting or pulling, and also to detect overall increases in total work related physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…In both the sub cohort with no neck pain at baseline, as well as the sub cohort with occasional neck pain at baseline, the loss to follow-up was 21 %. For selection bias to occur, both the prevalence of the exposure and the outcome has to differ between the drop-outs and those successfully followed, [ 30 ] which we find unlikely regarding the exposure leisure physical activity. Thus since we had almost an 80 % response rate we do not think that the validity of the study is affected to a notable extent.…”
Section: Discussionmentioning
confidence: 99%
“…Attrition in the GAZEL cohort is very low (0.6% were lost to follow-up by December 2013)8 and is not likely to modify the findings. It is nevertheless plausible that workers with difficult working conditions are more likely to have medical problems, as it has been shown that participants having serious health conditions are less prone to answer the annual questionnaire;10 failure to answer may have led to an underestimation of the association between high PPS and limitation in 2012.…”
Section: Discussionmentioning
confidence: 87%
“…However, global evaluation of physically arduous working conditions is complicated and raises many questions from a public health perspective 6 7. A recent study has indicated that a single self-reported variable of perceived physical strain (PPS) at work is a reliable and valid proxy measure for physical load at work 8. We aim here to study the association between a cumulative score based on PPS during working life and limitations after retirement in the GAZEL cohort.…”
Section: Introductionmentioning
confidence: 99%
“…These allowed the benefit of being brief, and may have improved response rates, but their simplicity may have obscured more nuanced potential responses by participants. 39 Single-item selfassessments have been found to be valid and reliable in evaluating perceptions of dementia in the elderly 40 and workplace physical stressors, 41 and in the current study provide initial validation to support intensifying our educational efforts.…”
Section: Discussionmentioning
confidence: 98%